Pola Arsitektur Enterprise Untuk Platform Investasi Bersama - D Doni; Teduh Dirgahayu (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
The Crowdfunding system offers a solution for micro, small, and medium-sized enterprises (MSMEs) to obtain business capital. Business owners acquire capital by selling a portion of their shares to investors through a crowdfunding platform. One of the platforms that implements the crowdfunding system is SANTARA and BIZHARE. The business process involves connecting business owners with investors on a single platform to exchange values. Typically, platform development focuses on regulation and creating new value, without considering the alignment between business processes and information technology (IT), resulting in suboptimal system processes. The use of enterprise architecture (EA) can bridge the gap between information technology (IT) and company business processes. Enterprise architects can use EA patterns as an effective solution in developing enterprise systems. This has an impact on saving time and resources, facilitating stakeholders in understanding EA, and enabling the representation of designs that can be reused and modified according to the needs of the system to be developed. The objective of this research is to model EA patterns in the Crowdfunding platform. The results of the EA pattern modeling will be evaluated by creating a prototype design and testing using the UAT method.